The co-morbidity of eating disorders and anxiety disorders: a review - Swinbourne, Jessica M.; Touyz, Stephen W. (European eating disorders review, 2007)
Objective To critically review the literature examining the co‐morbidity between eating disorders and anxiety disorders. Method A review of the literature on the co‐morbidity between anorexia nervosa, bulimia nervosa and eating disorders not otherwise specified and the anxiety disorders of OCD, PTSD, social anxiety, GAD, panic and agoraphobia. Results Of the empirical studies undertaken, it is clear that anxiety disorders are significantly more frequent in subjects with eating disorders than the general community. Researchers have shown that often anxiety disorders pre‐date eating disorders, leading to a suggestion that early onset anxiety may predispose individuals to developing an eating disorder. To date however, the research presents strikingly inconsistent findings, thus complicating our understanding of eating disorder and anxiety co‐morbidity. Furthermore, despite indications that eating disorder prevalence amongst individuals presenting for anxiety treatment may be high, there is a distinct lack of research in this area. Discussion This review critically examines the available research to date on the co‐morbidity of eating disorders and anxiety disorders. Some of the methodological limitations of previous research are presented, in order to highlight the issues which warrant further scientific investigation in this area. Copyright © 2007 John Wiley & Sons, Ltd and Eating Disorders Association.